MAGNETIC REDUCED GRAPHENE OXIDE AS ADVANCED MATERIALS FOR ADSORPTION OF METAL IONS - Andri Hardiansyah; Elsy Rahimi Chaldun; Amelia Fadyah Idzni (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2017)
MAGNETIC REDUCED GRAPHENE OXIDE AS ADVANCED MATERIALS FOR ADSORPTION OF METAL IONS. Magnetite (Fe₃O4) Reduced Graphene Oxide (MRGO) is graphene-based material that modified by introducing of Fe₃O4 nanoparticles onto the surface of graphene oxide (GO). MRGO exhibit some unique and advanced properties and characteristic including high surface area, superparamagnetic characteristics and adsorption ability against ions and molecules. In this research, GO was prepared by the Hummers method, followed by reacting FeCl₂.4H₂O and FeCl₃.6H₂O through co-precipitation method for the formation of magnetite nanoparticles on the graphene surface. MRGO was prepared with various composition of ferrochloride tetrahydrate (FeCl₂.4H₂O). Furthermore, the resultant of MRGO was characterized by Scanning Electron Microscope (SEM), Fourier-transform Infrared (FTIR) Spectroscopy, X-ray diffraction (XRD) and Atomic Adsorption Spectroscopy (AAS). Adsorption characteristics test was conducted against electroplating waste-based metal ion. The SEM results showed that GO exhibited the layered structure meanwhile MRGO exhibit as a Fe₃O4-modified GO layered surfaces. Furthermore, MRGO made by different ferrochloride tetrahydrate differed in the Fe₃O4 nanoparticles formation on the surface of GO. Increasing the composition of ferro chloride tetrahydrate increased the formation of Fe₃O4. MRGO developed as a superparamagnetic material which could easily interact during the external magnetic field applications and this character will easily disappears when the magnetic field is removed. Moreover, MRGO (FeCl₂.4H₂O 0.0064M) is successfully applied as nickel metal ion (Ni2+) adsorbents with the adsorption ability of 78,24%. This results showed that MRGO have a potential prospect as an effective and efficient adsorbent advanced material candidate.